Human Mesenchymal Stem Cells Prevent Neurological Complications of Radiotherapy - Soria, Bernat; Martin-Montalvo, Alejandro; Aguilera, Yolanda; Mellado-Damas, Nuria; López-Beas, Javier; Herrera-Herrera, Isabel; López, Escarlata; Barcia, Juan A.; Alvarez-Dolado, Manuel; Hmadcha, Abdelkrim; Capilla-González, Vivian (Frontiers in Cellular Neuroscience, 2019)
Radiotherapy is a highly effective tool for the treatment of brain cancer. However, radiation also causes detrimental effects in the healthy tissue, leading to neurocognitive sequelae that compromise the quality of life of brain cancer patients. Despite the recognition of this serious complication, no satisfactory solutions exist at present. Here we investigated the effects of intranasal administration of human mesenchymal stem cell (hMSCs) as a neuroprotective strategy for cranial radiation in mice. Our results demonstrated that intranasally delivered hMSCs promote radiation-induced brain injury repair, improving neurological function. This intervention confers protection against inflammation, oxidative stress, and neuronal loss. hMSC administration reduces persistent activation of damage-induced c-AMP response element-binding signaling in irradiated brains. Furthermore, hMSC treatment did not compromise the survival of glioma-bearing mice. Our findings encourage the therapeutic use of hMSCs as a non-invasive approach to prevent neurological complications of radiotherapy, improving the quality of life of brain tumor patients.